The Influence of Digital Convenience, Online Promotions, and Instant Gratification on Repurchase Intention among FEBI UINSU Students using Tiktok Shop - Annisa Rahmah Herlin; Nurbaiti; Muhammad Ikhsan Harahap (Media Ekonomi dan Manajemen, 2026)
This study aims to reveal how digital convenience, online promotions, and instant gratification tendency influence repurchase intention among students of the Faculty of Islamic Economics and Business at State Islamic University of North Sumatra who actively use TikTok Shop. Alongside the rapid growth of social commerce, consumer behavior patterns have undergone significant transformation, consequently making repurchase intention a critical indicator of platform sustainability in the digital marketplace. To address this objective, the study employed a quantitative approach based on explanatory research. Data were collected through questionnaires distributed to 108 respondents selected purposively according to predetermined criteria. The analytical technique applied was Partial Least Squares Structural Equation Modeling (PLS-SEM). The results showed that digital convenience and instant gratification tendency exerted a positive and significant influence on repurchase intention, while online promotions did not confirm a statistically meaningful effect. In conclusion, digital convenience and instant gratification proved to be dominant, while online promotions were not significant. These findings suggest that strengthening the quick-shopping experience is more crucial than promotional gimmicks in maintaining consumer loyalty on social commerce platforms. Theoretically, this study extends the application of the Theory of Planned Behavior to the social commerce context by demonstrating how digital convenience corresponds to perceived behavioral control and how instant gratification tendency reflects attitude toward behavior, offering novel insights into consumer behavior on short-form video-based platforms.